Mali Economic Update, Spring 2021 : Protecting the Vulnerable during the Recovery - World Bank (World Bank, Washington, DC, 2021)
The twin shocks of the pandemic and the coup pushed the economy into a recession in 2020. Real GDP is estimated to contract by 2.0 percent (4.9 percent in per capita terms) in 2020. The containment measures from mid-March to early May 2020 hampered economic activity in the sectors that source critical imports from abroad, depend on international traveling and those more reliant on face-to-face interactions for service delivery. On the demand side, private consumption declined, due to lower remittance inflows, households’ response to the health hazard, and containment measures. Non-priority public investment was curtailed to accommodate COVID-related expenditures, and donor disengagement after the military coup. Inflation picked up in May and continued to rise due to low cereal output and supply chain disruptions. The fiscal deficit increased to 5.5 percent of GDP in 2020. The pandemic’s economic toll and the slowdown in international trade slowed domestic revenues. Authorities responded with an ambitious COVID-19 emergency response plan (2.3 percent of GDP). Therefore, both the spending increases, and revenue shortfalls contributed to a higher fiscal deficit. Meanwhile, external support from international communities were delayed after the military coup. Public debt subsequently increased to 44.1 percent of GDP. Notwithstanding this increase, Mali remained at moderate risk of debt stress with some space toabsorb shocks (joint IMF/World Bank Debt Sustainability Analysis (DSA), February 2020). The crisis offers an opportunity to build back educational systems stronger and more equitable than before. As rules around social distancing are gradually relaxed, systems need to ensure that schools reopen safely, student dropout is minimized, and learning recovery starts. An immediate policy option to focus on is the development and implementation of remedial education, accelerated learning programs, and revision of the academic calendar and examination schedules to allow effective school continuity particularly in poor and conflict areas. Medium-term policies in the aftermath of the pandemic will be the: (i) enhancement of the immediately established remote learning platforms within the ministry of national education and (ii) development of digital teaching content for each education level in full alignment with the existing curricula. Longer term policies would be to establish a virtual library with an inventory of national and international teaching resources to be used for remote learning programs to be delivered through existing channels (radio, television, mobile phone, and internet). These policies would make the country resilient to future disruptions. Given limited resources, policy prioritization, effective implementation should be emphasized and in line with a general framework of medium-term fiscal consolidation. A COVID-19 response plan was put in place in April 2020, with an uneven level of implementation. Lessons should be learnt with improved oversight of COVID-19 fund execution. Meanwhile, the enduring structural deficit and increasing resort to domestic short-term financing add to the risks on fiscal sustainability, which is further aggravated by the 2020 twin crises. The broad direction for fiscal policy changes points to the need to mobilize more domestic revenue and reform public spending to increase the fiscal space for higher quality services and investments, while reducing the overall deficit.